Planning The Needs of Jackfruit Chips using The Material Requirement Planning (MRP) Method At CV Puri Pangan Lestari Malang City - Dyan Fransiska Agata; Sri Tjondro Winarno; Pawana Nur Indah (Universitas Darussalam Gontor, 2024)
CV Puri Pangan Lestari does not produce jackfruit chips when it is not harvesting season. The instability or unavailability of jackfruit is caused by the insufficient order quantity when it is not harvesting time because the company only has 1 raw material supplier. It’s necessary to raw material planning for jackfruit chips at CV Puri Pangan Lestari. This study aims to analyze raw material planning for jackfruit chips at CV Puri Pangan Lestari Malang City. Raw material planning using the Material Requirement Planning (MRP) method with lot sizing techniques LFL, EOQ, and POQ. The results showed that CV Puri Pangan Lestari can do jackfruit chips raw material planning using the LFL method MRP calculation because the inventory cost is smaller than the EOQ and POQ methods. Calculation of total inventory with the LFL method on jackfruit chips at CV Puri Pangan Lestari amounted to IDR.17,850,000.